Vegetation Analysis of Namuna Community Forest of Salbari, Sanischare VDC in Jhapa District, Eastern Nepal - Bhattarai, Krishna Prasad (Journal of Natural History Museum, 2009)
Vegetation study was carried out in an afforested land called Namuna Community Forest in Salbari, Sanischare, VDC, Jhapa, District. Random samplings for estimation of density, frequency, basal area and IVI were carried out by laying quadrates (10m x 10 m) at different sites of forest, three times and mean value was calculated. Nine tree species were recorded during field study. Total density of 10,410 pl/ha and total basal area of 33.956 m2/ha of tree species were recorded. The value of density (1790 pl/ha), basal area (31.45m2/ha) and IVI (130.63) were found highest for Shorea robusta, which is ecologically successful species in this forest. Lower value of basal area showed that this forest is young and regenerating. Other tree species had comparatively lower value of density, basal area and IVI due to regular human inte rference. Therefore an example of establishing forest community so as to initiate the conservation of local biodiversity has been discussed in this article. Key words: Community forest; conservation; IVI estimation; regenerating; Shorea robusta Journal of Natural History Museum Vol. 23, 2008 Page 12-15